Assessment of tolerance to psychophysical load in students of a special medical group during nordic walking classes - Minnikaeva N.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess tolerance to psychophysical stress in students of a special medical group based on indicators of the functional state of the cardiovascular system and subjective assessment on the pain scale. Methods and structure of the study. A training program based on Nordic walking was developed, 12 sessions were conducted, during which tolerance to psychophysical stress was monitored by tracking objective and subjective indicators. The study involved 126 people, of which 76 girls and 50 boys, all belonging to the third health group (A), the average age at the time of the study was 18.2 years. Results and conclusions. The results obtained indicate that adaptation to psychophysical stress among SMG students is positive if organizational, methodological and medical-biological factors are observed, including monitoring the functional state of the cardiovascular system in the form of pedagogical control and psycho-emotional background through assessment on a behavioral pain scale.